Learning English Through Non-English Subjects: A Survey on Nepalese EFL Students - Wagle, Bashu Dev (The Batuk, 2024)
In Nepal, students are taught various subjects using two different mediums of instruction. The majority of teachers prefer using English as the medium of instruction, but there are still some who opt for their mother tongue. This research aimed to investigate the impact of teaching English through non-English subjects on the vocabulary development of Nepalese EFL students. A total of seventy-four students participated in this study and were divided into two groups: one group learned English through non-English subjects (SLETNES) as the experimental group, while the other group learned non-English subjects in their mother tongue (SLNESMT) as the control group, based on teachers’ preferences for the medium of instruction. Both groups of students completed a questionnaire, and the data collected were analyzed to determine which group exhibited better vocabulary learning outcomes. The study spanned four sessions, with each session lasting 40 minutes. The data analysis revealed a significant difference between the two groups, with SLETNES students being exposed to a more extensive vocabulary.